Molecular Cloning and Comparative Analysis of a PR-1-RK Hybrid Gene from Triticum urartu, the A-Genome Progenitor of Hexaploid Wheat - Lu, Shunwen; Faris, Justin D.; Edwards, Michael C. (Plant molecular biology reporter, 2018)
Wheat genomes encode pathogenesis-related protein 1 (PR-1)/receptor-like kinase (RK) hybrid proteins as first reported for hexaploid wheat. To date, no PR-1-RK-like proteins have been identified in the diploid wild wheat Triticum urartu , the A-genome progenitor of hexaploid wheat. Here, we report the cloning and characterization of a PR-1-RK hybrid gene ( TuPr-1-rk) and a related pseudogene ( TuPr-1-rkP ) from T. urartu and comparative analysis of the wheat Pr-1-rk genes. TuPr-1-rk and TuPr-1-rkP were found to distribute independently among the natural populations of T. urartu , and the accession G1812 (the source of the published genome) was found to contain TuPr-1-rkP only. Sequence analysis revealed that TuPr-1-rkP originated from TuPr-1-rk through repetitive DNA-associated recombination. Transcriptional analysis confirmed that TuPr-1-rk is expressed in response to salinity stress and pathogen attack and is subject to alternative splicing (AS) as are the Pr-1-rk genes in hexaploid wheat, whereas TuPr-1-rkP is completely silenced. Thirteen AS-derived TuPr-1-rk mRNA isoforms were identified, and a comparable abundance was found between one encoding the full-length protein and those encoding C-terminally truncated proteins. Comparative analysis revealed that the wheat PR-1-RK proteins are highly conserved despite the substantial genomic variations of the coding genes. The identification of the TuPr-1-rk gene adds an important ancestral member to the wheat PR-1-RK gene family, and the observed commonality in expression patterns and the conservation of the PR-1-RK proteins support the notion that the Pr-1-rk gene may play important roles in stress response-related pathways in wheat.